If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = 3x + 15 Reorder the terms: 12 + 4x = 3x + 15 Reorder the terms: 12 + 4x = 15 + 3x Solving 12 + 4x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 4x + -3x = 15 + 3x + -3x Combine like terms: 4x + -3x = 1x 12 + 1x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 1x = 15 + 0 12 + 1x = 15 Add '-12' to each side of the equation. 12 + -12 + 1x = 15 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 15 + -12 1x = 15 + -12 Combine like terms: 15 + -12 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 2p^2=12p+54 | | x-3*y=4 | | 4z-2=7+1 | | 3s^2-13s=-12 | | x-3y=4 | | x^2+12x+26=27 | | 1.26=-1.44 | | 9x=-6x-30 | | 4y+16=3.3y-1.3 | | s^2+9s=-20 | | x/5-9=9 | | 75a^3+90a^2+27a=0 | | w/3+18=21 | | 38.5=9/5(F-32) | | 5x=9x-15 | | k+23.7=23.7 | | 30x^2+5x-10=0 | | y=4x-4 | | F=9/5(38.5-32) | | X^2+10x+25=36 | | 2r^2+392=56r | | 6n-1=5n-7 | | 8x+24=12x | | 38.5=5/9(F-32) | | x^4-3x^2-8x^3=0 | | 6y=4y^2 | | 16x+280=8x^2 | | -6z-(2x+8)+10z= | | 12x^2-3x-1=0 | | 900x^2=625 | | 5x^2-9x-18=0 | | 41-8x-9=-6x-9-23 |